Specific probiotic therapy attenuates antibiotic induced visceral hypersensitivity in mice. Issue 2 (16th August 2005) - Verdú, E F; Bercik, P; Verma-Gandhu, M; Huang, X-X; Blennerhassett, P; Jackson, W; Mao, Y; Wang, L; Rochat, F; Collins, S M
Abstract : Background and aim: Abdominal pain and discomfort are common symptoms in functional disorders and are attributed to visceral hypersensitivity. These symptoms fluctuate over time but the basis for this is unknown. Here we examine the impact of changes in gut flora and gut inflammatory cell activity on visceral sensitivity. Methods: Visceral sensitivity to colorectal distension (CRD) was assessed at intervals in healthy mice for up to 12 weeks, and in mice before and after administration of dexamethasone or non-absorbable antibiotics with or without supplementation with Lactobacillus paracasei (NCC2461). Tissue was obtained for measurement of myeloperoxidase activity (MPO), histology, microbiota analysis, and substance P (SP) immunolabelling. Results: Visceral hypersensitivity developed over time in healthy mice maintained without sterile precautions. This was accompanied by a small increase in MPO activity. Dexamethasone treatment normalised MPO and CRD responses. Antibiotic treatment perturbed gut flora, increased MPO and SP immunoreactivity in the colon, and produced visceral hypersensitivity. Administration of Lactobacillus paracasei in spent culture medium normalised visceral sensitivity and SP immunolabelling, but not intestinal microbiota counts. Conclusion: Perturbations in gut flora and in inflammatory cell activity alter sensory neurotransmitter content in the colon, and result in altered visceral perception. Changes in gut flora may be a basis for the variability of abdominal symptoms observed in functional gastrointestinal disorders and may be prevented by specific probiotic administration.